(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the views of the creator, the expression of thoughts and feelings in the artistic text using phraseological units, and special attention is paid to its analysis in linguopoetic studies through important linguistic evidence. Also, this article focuses on the skill of using phraseology in the poetry of the scientist and poet Siddiq Momin, and the weight of phraseological units and the expression of content in his creative products are highlighted. It has been determined that the charm of poetic expressions is realized through phraseological units